Improving employee performance through compensation in savings and loans cooperatives - Sonny Hersona; Yamarthin Partogi Tarihoran; Sari Sekarini; Vicky Alvin Nugraha; Hilmy Muhammad Iqbal (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This research aims to investigate the influence of competency on employee performance at SLC Online Jaya Mandiri Karawang. A total of 32 SLC staff were used as the research population, and the entire population was interviewed using the census method (Sample Sum). Observation, questionnaire, and documentation methods were used for data collection. Data analysis involves testing validity, reliability, simple regression, and coefficient of determination. The results of the analysis show that there is a correlation between salary and bonuses and the performance of SLC Online Jaya Mandiri Karawang employees, measured through a validity test. The rcount value which is greater than the rtable value (0.349) indicates adequate validity. The reliability test shows that all variables have a confidence value greater than the reliability standard of 0.60. A simple regression test shows the relationship between salary variables and employee performance, with the formula Y = 3.076 x 0.549 and significance less than 0.05. The coefficient of determination of 43.2% shows that 43.2% of employee performance is influenced by salary variables. The remaining 56.8% was influenced by other factors not tested in this study. The research results provide the implication that increasing salaries can have a positive impact of 43.2% on the performance of SLC Online Jaya Mandiri Karawang employees. However, it should be noted that other factors not tested also played an important role at 56.8%. Therefore, further recommendations for future research could involve additional variables to understand other factors that influence employee performance in a more holistic manner.